2008
DOI: 10.1088/0953-4075/42/2/025202
|View full text |Cite
|
Sign up to set email alerts
|

Screening effects and total cross sections of single, double and triple ionization of neon by fast electrons

Abstract: The Bethe–Born theory is applied to estimate the effective charges experienced by the ejected electrons at single, double and triple ionization of neon by fast electrons. The expansion coefficients appearing in the asymptotic expressions for total cross sections σn+ ∼ [an+ln(Ei/In+) + bn+]/Ei are determined by fitting to these expressions the experimental data for single and multiple ionization of neon. Coefficients an+ and bn+ are seen to decrease exponentially with increasing number of ejected electrons. Emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The values of K [see Eqs. (4) and (20)] are indicated in the figure captions. Figures 1(a), 2(a), and 3(a) give the results of our calculations with electron correlations treated fully in both the initial and the final states for various pairs of electron energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of K [see Eqs. (4) and (20)] are indicated in the figure captions. Figures 1(a), 2(a), and 3(a) give the results of our calculations with electron correlations treated fully in both the initial and the final states for various pairs of electron energy.…”
Section: Resultsmentioning
confidence: 99%
“…electron ejection following the emission of a first slow electron after a direct collision of the projectile with the target electron is not clear. A theoretical analysis of the matrix element requires the calculation of n > 2 electron continuum wave functions; this problem is not properly solved (see, for example, [4]). …”
Section: Introductionmentioning
confidence: 99%
“…This conclusion forces us to assume that there are strong correlations among slow electrons in the final state of the reaction, which calls for a dedicated examination. An attempt at such a study was made in [72] within the framework of the effective charge method and looks effective, although still complicated if it were to be carried out in actual calculations.…”
Section: Multiple Ionization Of Noble Gas Atoms By a Fast Electronmentioning
confidence: 99%
“…In addition, we assume that the remaining electrons in the doubly charged ion core are unaffected by the ionization process. Under these conditions, the initial state of the system is characterized by the product of an incident plane wave with a molecular target wave function while the final state is described by the product of a scattered plane wave with two independent Coulomb wave functions as well as an approximate expression of the Gamov factor for modeling the electron-electron repulsion [24,25]. Finally, in order to go beyond the domain of validity of the first Born approximation and then to extend the current water molecule double ionization modeling down to the intermediate energy regime, we followed the recommendations of Behati et al who suggested to use an approximate Coulomb wave function of effective charge Z* to represent the scattered electron in the field created by the water nucleus together with the two ejected electrons [26][27][28].…”
mentioning
confidence: 99%
“…where gG(k\ , k2) refers to the approximate expression for the repulsive Gamov factor given by Defrance and co-workers [24,25]:…”
mentioning
confidence: 99%